2021
DOI: 10.21273/hortsci15827-21
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Global Research on Muskmelon (Cucumis melo L.) Based on Web of Science

Abstract: Muskmelon is a warm season cucurbit species that belongs to family Cucurbitaceae. We analyzed 2955 papers of global research on muskmelon (Cucumis melo L.) based on Web of Science from 1924 to 2021. Papers were mainly written in English (2766, 93.604%), from 7883 authors, 83 countries or regions, 1697 organizations, and published in 585 journals and book series. The top five journals were HortScience (334, 11.303%), Journal of the American Society for Horticultural Science (Proceedings of the American Society … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In another study [ 45 ], when Melon ( Cucumis melo L) research in the horticulture category was compared with the top 10 journals in this study, it was found that only the "Journal of Agricultural and Food Chemistry" was in the top 10, and the other journals were different. The most productive authors, the institutions that publish the most articles, and the most frequently used keywords are completely different from the results in this study.…”
Section: Discussionmentioning
confidence: 72%
“…In another study [ 45 ], when Melon ( Cucumis melo L) research in the horticulture category was compared with the top 10 journals in this study, it was found that only the "Journal of Agricultural and Food Chemistry" was in the top 10, and the other journals were different. The most productive authors, the institutions that publish the most articles, and the most frequently used keywords are completely different from the results in this study.…”
Section: Discussionmentioning
confidence: 72%
“…The relationships between the articles and the VOSviewer program were used to analyze the findings on the strength of the relationships. The visualizations created with the help of this program carry out the collaboration of authors, institution(s) and countries, and related research topics, as well as the association of publications on the data obtained from the WoS database (Yuan et al, 2021). Researchers in bibliometric analysis frequently prefer VOSviewer software.…”
Section: Discussionmentioning
confidence: 99%
“…A bibliometric analysis is a statistical evaluation of published productions, and it is used to measure the influence of publications, scholars or institutions in the scientific community. The bibliometric technique has already been employed in several research areas such as grafting in horticultural plants [44], in potato [45], in cucumber sativus [46] and Cucumis melo [47], and in essential oil-bearing plants under water stress [48].…”
Section: Data Collection and Analysismentioning
confidence: 99%